Going forward from B to A? Proposals for the Eurozone crisis - Massimo Amato; Luca Fantacci; Dimitri B. Papadimitriou; Gennaro Zezza (Levy Economics Institute of Bard College, 2016)
After reviewing the main determinants of the current eurozone crisis, this paper discusses the feasibility of introducing fiscal currencies as a way to restore fiscal space in peripheral countries, like Greece, that have so far adopted austerity measures in order to abide by their commitments to eurozone institutions and the International Monetary Fund. We show that the introduction of fiscal currencies would speed up the recovery, without violating the rules of eurozone treaties. At the same time, these processes could help transition the euro from its current status as the single currency to the status of "common clearing currency," along the lines proposed by John Maynard Keynes at Bretton Woods as a system of international monetary payments. Eurozone countries could therefore move from "Plan B," aimed at addressing member-state domestic problems, to a "Plan A" for a better European monetary system.
Keywords: E02; E12; E42; F45; 330; Euro; Fiscal Currencies; Austerity; Current Account Imbalances; Clearing Union